Possession of Land - Wonnacott, Mark (Cambridge University Press, 2013)
It has been said, rightly, that there is no law of ownership of land in England andWales, only a law of possession.1 Yet ‘difficult problems arise in English real property law on the concept of possession’.2 The following chapters explore some of these problems, and suggest some solutions. But this chapter is concerned with the principal cause of those problems; the different meanings, and inconsistent usage, of the term ‘possession’ in English land law.